The Impact of Digital Financial Literacy on Investment Decisions in Mutual Funds and Money Markets among Millennials - Didin Fatihudin; Fitria Ningrum Sayekti; Murdiani Sukarana; Rekno Sulandjari; Gregorius Paulus Tahu (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The rapid growth of digital financial services has transformed how individuals manage and invest their money, particularly among millennials who are more inclined to use online platforms for financial transactions. This study investigates the impact of digital financial literacy on investment decisions in mutual funds and money markets among millennials. As digital platforms become increasingly prevalent, understanding how millennials’ financial literacy affects their ability to make informed investment choices is crucial. The research employs a library research method, analyzing secondary data from scholarly articles, books, and previous studies. The findings indicate that millennials with higher levels of digital financial literacy make more informed and strategic investment decisions, demonstrating improved risk management and better use of digital platforms. In contrast, those with lower financial literacy are more prone to impulsive decisions and external influences. The study concludes that enhancing digital financial literacy is essential for empowering millennials to make responsible investment choices, thereby contributing to better financial outcomes and sustainable wealth building. These findings imply that policymakers, educators, and financial institutions should prioritize digital financial education programs to strengthen millennials’ decision-making capabilities and promote long-term financial stability.